The Making of the Humanities Volume 1- Early Modern Europe - Bod, Rens; Maat, Jaap; Weststeijn, Thijs (Amsterdam University Press, 2010)
This book is the first step towards the development of a comparative history of the humanities. Specialists in philology, musicology, art history, linguistics, literary theory, and other disciplines highlight the intertwining of the various fields and their impact on the sciences. This first volume in the series The Making of the Humanities focuses on the early modern period. Different perspectives reveal how the humanities developed from the 'liberal arts', via the curriculum of humanistic schools, to modern disciplines. The authors show in particular how discoveries in the humanities contributed to a secular world view, pointing up connections with the scientific revolution. The main themes are: the humanities versus the sciences; the visual arts as liberal arts; humanism and heresy; language and poetics; linguists and logicians; philology and philosophy; the history of history. Contributions come from a selection of internationally renowned European and American scholars, including Floris Cohen, David Cram, and Ingrid Rowland. The book offers a wealth of insights for specialists, students, and those interested in the humanities in a broad sense. This title is available in the OAPEN Library - http://www.oapen.org.